Geographic Properties of Internet Routing: Analysis and Implications - Lakshminarayanan, Subramanian; Padmanabhan, Venkat; Katz, Randy H. (2001)
In this paper, we study the geographic properties of Internet routing. Our work is distinguished from previous studies of Internet routing in that we consider the geographic path traversed by packets, not just the network path. We examine several geographic properties, including how circuitous Internet routes tend to be, how multiple ISPs along an end-to-end path share the burden of routing packets, and how much sharing there is between paths at the geographic level. We evaluate these properties using extensive network measurements. We examine both the spatial and the temporal variations of some of the properties. We discuss the implications of these geographic properties and conclude that geography is an interesting tool for analyzing the Internet properties.